1995
DOI: 10.1128/mcb.15.5.2547
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic Nickel Silences Gene Expression by Chromatin Condensation and DNA Methylation: a New Model for Epigenetic Carcinogens

Abstract: A transgenic gpt+ Chinese hamster cell line (G12) was found to be susceptible to carcinogenic nickel-induced inactivation of gpt expression without mutagenesis or deletion of the transgene. Many nickel-induced 6-thioguanine-resistant variants spontaneously reverted to actively express gpt, as indicated by both reversion assays and direct enzyme measurements. Since reversion was enhanced in many of the nickel-induced variant cell lines following 24-h treatment with the demethylating agent 5-azacytidine, the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
250
0
6

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 357 publications
(264 citation statements)
references
References 76 publications
8
250
0
6
Order By: Relevance
“…Previous studies of the effect of nickel on transgene silencing in cell culture showed that nickel exposure of transgenic Chinese hamster G12 cells resulted in transgene silencing (Lee et al, 1993). This nickel-induced transgene silencing did not involve mutation or deletion of any portion of the transgene (Lee et al, 1995). Instead, increased DNA methylation and chromatin condensation (Lee et al, 1995), as well as a broad loss of histone acetylation of all four core histones and an increase in histone H3K9 methylation were observed at the silenced transgene locus (Yan et al, 2003;Ke et al, 2006).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous studies of the effect of nickel on transgene silencing in cell culture showed that nickel exposure of transgenic Chinese hamster G12 cells resulted in transgene silencing (Lee et al, 1993). This nickel-induced transgene silencing did not involve mutation or deletion of any portion of the transgene (Lee et al, 1995). Instead, increased DNA methylation and chromatin condensation (Lee et al, 1995), as well as a broad loss of histone acetylation of all four core histones and an increase in histone H3K9 methylation were observed at the silenced transgene locus (Yan et al, 2003;Ke et al, 2006).…”
Section: Discussionmentioning
confidence: 82%
“…However, the mechanisms of tumor formation by nickel exposure remain unclear. Nickel compounds are found to be nonmutagenic in most conventional mutagenesis assays (Biggart and Costa, 1986;Biedermann and Landolph, 1987;Miura et al, 1989;Kargacin et al, 1993), but an epigenetic mechanism has been hypothesized to explain the potent carcinogenic effects of nickel ions (Lee et al, 1995;Broday et al, 1999;Sutherland et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have demonstrated that exposure to nickel causes CpG island methylation. 31,32 In addition to exogenous agents, endogenously-produced materials, including reactive oxygen species, are suspected as possible causes for aging-related methylation in the stomach. 10,33 Epithelial cell injury, caused by H. pylori, implicates several pathways, with oxygen-radical injury being one.…”
Section: Discussionmentioning
confidence: 99%
“…Such events could probably induce abnormal methylation following treatment with somè nongenotoxic' carcinogens (Costa, 1995). For instance, in mouse cells reversible heterochromatinization can be promoted by some nickel compounds which can interact directly with histone H1 and induce local de novo methylation which is stable (Lee et al, 1995). Interestingly,`epimutations' are now considered a possible factor, which may cause imprinting defects in some sporadic Prader-Willi and Angelman syndrome cases (BuÈ rger et al, 1997;Buiting et al, 1998).…”
Section: Introductionmentioning
confidence: 99%